Tinjauan Kritis-Multifaset Terhadap Tuduhan Genosida Atas Catatan Penaklukan Kuno Tanah Perjanjian - Yohanes, Hendra (Sekolah Tinggi Teologi SAAT, 2019)
Critical-Multifaceted Review Against Genocide Allegations of Ancient Conquest Account of the Promised Land. The purpose of this article is to deliver a critical-multifaceted review against the accusation that the Judeo-Christian God has commanded genocide to Israelites in the conquest of the Promised Land. Correspondingly, I try to reconsider what matters essentially in the accusation and dissect the accusation into three facets, included legal terminology, interpretive and moral-philosophical facets. By analyzing the criteria of genocide in international law, I argue that the ancient conquest account of the Promised Land in the Old Testament dissatisfies these criteria, thus the conquest was incorrectly classified as genocide. I also gather some examples of misinterpretation of the conquest account of the promised land. I agree that the figurative-hyperbolic language as a common literary feature in the ancient conquest account and the ideology of war viewed as the divine retribution in ancient near eastern worldview. Then, I take Joshua chapters 9-11 as a biblical case study to demonstrate historical-cultural gaps between the ancient near eastern context of the conquest account and our present context. In the last facet, I tersely argue that there is a more contextual approach based on theistic moral argument instead of the New Atheist accusation.